2019
DOI: 10.1002/mc.22979
|View full text |Cite
|
Sign up to set email alerts
|

MIF promotes perineural invasion through EMT in salivary adenoid cystic carcinoma

Abstract: Macrophage migration inhibitory factor (MIF) is a prominent orchestrator during the onset and progression of cancer. Recently, MIF was detected in salivary adenoid cystic carcinoma (SACC). However, its functional effect in perineural invasion (PNI) of SACC remained unknown. To illuminate the effect of MIF in genesis of PNI in SACC, we examined the expression of MIF, epithelial‐to‐mesenchymal transition (EMT)‐related markers, and Schwann cell markers by immunohistochemical analysis in 158 cases of SACC samples.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…For example, Yang et al found that MIF can drive the malignant progression of pancreatic cancer [ 16 ]. Zhang et al found that MIF can promote the perineural infiltration of salivary adenoid cystic carcinoma [ 17 ]. Wang et al found that AREG can regulate the epithelial-mesenchymal transition of pancreatic carcinoma cells [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Yang et al found that MIF can drive the malignant progression of pancreatic cancer [ 16 ]. Zhang et al found that MIF can promote the perineural infiltration of salivary adenoid cystic carcinoma [ 17 ]. Wang et al found that AREG can regulate the epithelial-mesenchymal transition of pancreatic carcinoma cells [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the BDNF/TRKB axis is also reported to have a role in the epithelial-mesenchymal transition (EMT) process in SACC. And the study by Mei Zhang et al proposed a correlation between PNI and MIF expression that MIF may promote the PNI of SACC by participating in cytoskeletal reorganization and pseudopod formation induced by Schwann-like cell differentiation of EMT and SACC cells ( 59 ). Despite the limited number of studies concerning the association between EMT and PNI, EMT is likely to play an invasive critical role in PNI progression, given the enhanced migration and abilities of cancer cells after EMT ( 42 ).…”
Section: The Perineural Niche and Tumor Microenvironment In Pnimentioning
confidence: 99%
“…Hoffmann et al and his colleagues reported that IL-6 serum levels increased in some SACC patients, compared with healthy controls [40]. Besides IL-6, other cytokines may contribute to SACC invasion and metastasis, such as transforming growth factor-β1 [41], macrophage migration inhibitory factor [42], and tumor necrosis factor receptor-associated factor 6 [43], et al Further studies are necessary to elucidate the exact roles of cytokines on SACC invasion. IL-6 exerts its biological functions by binding to its receptor sIL-6R to activate JAK/STAT3 signaling pathway, which controls the occurrence and development of tumors [44][45][46].…”
Section: Discussionmentioning
confidence: 99%